1998
DOI: 10.1074/jbc.273.10.5932
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Bacillus subtilis PyrR, a Bifunctional pyr mRNA-binding Attenuation Protein/Uracil Phosphoribosyltransferase

Abstract: Bacillus subtilis PyrR has been shown to mediate transcriptional attenuation at three separate sites within the pyrimidine nucleotide biosynthetic (pyr) operon. Molecular genetic evidence suggests that regulation is achieved by PyrR binding to pyr mRNA. PyrR is also a uracil phosphoribosyltransferase (UPRTase). Recombinant PyrR was expressed in Escherichia coli, purified to homogeneity, physically and chemically characterized, and examined with respect to both of these activities. Mass spectroscopic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 35 publications
2
62
0
Order By: Relevance
“…This regulation can occur by a variety of different mechanisms. For instance, aconitase and uracil phosphoribosyltransferase are regulatory enzymes that bind RNA (29,30). Proline oxidase and biotin synthetase contain separate DNAbinding domains that allow these proteins to function as transcriptional repressors (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…This regulation can occur by a variety of different mechanisms. For instance, aconitase and uracil phosphoribosyltransferase are regulatory enzymes that bind RNA (29,30). Proline oxidase and biotin synthetase contain separate DNAbinding domains that allow these proteins to function as transcriptional repressors (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was unexpected because the deduced amino acid sequences of PyrR proteins from various bacteria bear no significant sequence similarity outside of a short sequence in the active site to the sequences of previously characterized bacterial UPRTases, which are encoded by upp genes (1). Nonetheless, purified B. subtilis PyrR, when assayed under optimal conditions, has a UPRTase-specific activity comparable with purified bacterial upp-encoded UPRTases (8). Furthermore, the three-dimensional structure of B. subtilis PyrR, which was solved at high resolution by Tomchick et al (9), demonstrated that the PyrR structure is very similar to other Type I phosphoribosyltransferases (10).…”
mentioning
confidence: 96%
“…This was the case throughout the pH range from 7.2 to 9.7 and at all substrate concentrations studied. Values for the maximal velocity and Michaelis constants for PRPP and uracil from pH 7.7 to 9.7 have been previously published (8). A Ping Pong kinetic pattern is characteristic of enzymes that form a covalent intermediate with a portion of a substrate molecule, which in the case of UPRTase would indicate the following mechanism.…”
Section: Pyrr-catalyzed Uprtase Displays a Ping Pong Kinetic Patternmentioning
confidence: 99%
See 2 more Smart Citations